2000
DOI: 10.1128/mcb.20.9.3234-3244.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cid1, a Fission Yeast Protein Required for S-M Checkpoint Control when DNA Polymerase δ or ɛ Is Inactivated

Abstract: The S-M checkpoint is an intracellular signaling pathway that ensures that mitosis is not initiated in cells undergoing DNA replication. We identified cid1, a novel fission yeast gene, through its ability when overexpressed to confer specific resistance to a combination of hydroxyurea, which inhibits DNA replication, and caffeine, which overrides the S-M checkpoint. Cid1 overexpression also partially suppressed the hydroxyurea sensitivity characteristic of DNA polymerase ␦ mutants and mutants defective in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
61
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 48 publications
0
61
0
Order By: Relevance
“…S. pombe pol ⑀ may indirectly participate in the DNA damage response through an interaction with cid1 ϩ . Only cdc20cid1 double mutants, but not either single mutant, show a substantial loss of viability and the appearance of the "cut" phenotype, which indicates aberrant entry into mitosis (36).…”
mentioning
confidence: 99%
“…S. pombe pol ⑀ may indirectly participate in the DNA damage response through an interaction with cid1 ϩ . Only cdc20cid1 double mutants, but not either single mutant, show a substantial loss of viability and the appearance of the "cut" phenotype, which indicates aberrant entry into mitosis (36).…”
mentioning
confidence: 99%
“…The similarity between GLD-2 and Cid1 is particularly striking, as both are involved in cell cycle control. GLD-2 promotes entry into meiosis at the expense of mitosis 4 , and Cid1 inhibits mitosis 23 . We suggest that GLD-2 and Cid1 may in fact be components of an ancient regulatory circuit controlling the cell cycle, and that other GLD-2 relatives may similarly be regulatory cytoplasmic PAPs.…”
mentioning
confidence: 99%
“…Like Zcchc11, Cid1 is a cytoplasmic uridyltransferase (6,29) that contributes to cell proliferation (7)(8)(9). However, substantial differences do exist.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have shown that Zcchc11 promotes G 1 -to-S phase progression, whereas both the yeast and C. elegans Cid1 proteins act primarily in stressed cells to control the G 2 -to-M checkpoint (7)(8)(9). Furthermore, in yeast, the cell cycle regulatory activity of Cid1 is dependent on its uridyltransferase activity, although its uridylation targets have not been identified (8,9). Conversely, we have shown here that the proliferative activity of Zcchc11 is independent of its uridyltransferase domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation